Edukasi Cuci Tangan Pakai Sabun pada Siswa Sekolah Dasar Negeri Podosoko 1, Sawangan, Magelang - Nazwa Safitri, Alysa; Stevani Sinaga, Angelina; Maharani, Nathasya Anggieta; Candra Saputra, Zulfikar; Widaniswari Widi Wijaya, Renata; Hanifah Putri, Rengganis (Universitas Baiturrahim, 2025)
The issue of stunting in Indonesia is one of the main priorities of the Indonesian government. Stunting can have negative impacts on children's cognitive development. Based on secondary data from the Sawangan II Community Health Center, the stunting rate has reached 14.9%. One of the efforts to prevent stunting is through community service focused on improving the implementation of PHBS. The practice of CTPS is one component of PHBS. Based on observations conducted, students at SDN Podosoko 1 still have low levels of knowledge regarding the importance of washing hands with soap. Therefore, an effort to address this issue is by providing CTPS education, aimed at increasing knowledge so that students can consistently apply it in their daily lives. This, in turn, can raise awareness of PHBS in the community and help reduce the incidence of stunting. The method used includes education and demonstrations supported by posters and songs. The activity went smoothly, and the children were very enthusiastic and showed great skill in practicing it in their daily lives